The EFS Program to Enhance Students' Speaking Skills For Daily Conversation : (Study Case at MAN 1 Bandar Lampung) - Ma'rifatul Halimatus Sa’diyah; Desi Purpitasari (English Education Department - Universitas Nasional Karangturi, 2023)
This study aims to investigate implementing the